Highly Selective Molecularly Imprinted Polymer Sensor for Indium Detection Based on Recognition of In‐Alizarin Complexes. Issue 7 (21st April 2015) - Zhang, Lianming; Li, Jianping; Zeng, Ying; Meng, Linghao; Fu, Cong
Abstract A highly selective molecularly imprinted polymer electrochemical sensor for In3+ detection was proposed. In3+ ion was chelated with alizarin red S to form a complex In‐ARS. The complex was used as the template molecule to prepare a molecularly imprinted polymer (MIP) based sensor. The selectivity of the sensor was improved significantly due to the three‐dimensional specific structure of the complex, and the selective complexation of ligands for metal ions. Moreover, the sensitivity of the proposed sensor was improved by recording the reductive current of ligand in complex. This technique was highly sensitive for quantitative analysis of In3+ in the concentrations ranged from 1×10−8 mol/L to 2.5×10−7 mol/L with a detection limit of 4.7×10−9 mol/L. The proposed sensor has been successfully used in detecting In3+ in real samples.